Mercado del sexo: Reflexiones desde la economía al comercio sexual (2013)
This paper is an approach to sex market and those who develop primarily (sex workers), identifying the theoretical contributions that have been proposed since the economy through its various paradigms, from theoretical as institutionalism, the neoclassical theory and human capital. Through this document looming gaps in traditional theoretical explanations of the economy in the exploration of trade and sex work in the context of the labor market in the contemporary world, opening a discussion of field phenomena such as gender discrimination in the economics.